The Construction of Women's Power in the Film Hati Suhita - Agustina; Inayah Rohmaniyah; Rizki Putriani (Yinyang: Jurnal Studi Islam Gender dan Anak, 2025)
This article examines the construction of women's power within the context of Islamic boarding schools (pondok pesantren), using the film Hati Suhita as a case study. Employing content analysis and Mansour Fakih's theory of gender, this study explores the historical, social, and cultural influences on the perception of women's power. The film reveals that the construction of women’s authority in pesantren is shaped by both internal and external forces that have traditionally relegated women to subordinate roles. However, Hati Suhita illustrates that gender constructions are not fixed. The character Alina Suhita challenges traditional norms, presenting a compelling narrative in which women can occupy roles equal to men. The acknowledgment of women’s power in the film reflects a positive influence, particularly in education and leadership. The findings highlight the importance of transforming discriminatory gender constructs, a goal achievable through education, advocacy, and policy reform. This study provides significant insight into how gender dynamics in Islamic educational settings can evolve to support greater inclusion and empowerment.